Steering System Design for the Marapi Electric Car Politeknik Negeri Padang - Candra Mayana, Hendri; Hanif (Universitas Negeri Padang, 2024)
This research aims to design and build a steering system for electric cars at the Padang State Polytechnic. This design is focused on meeting the minimum turning radius requirement of 6 meters in accordance with the KMHE 2023 regulations, with the aim of demonstrating compliance with expected safety and maneuverability standards. The steering system used is Rack and Pinion, which has proven to be effective in controlling the turning angle of the wheels with the turning angle of the inside front wheel being 15.74º and the outside front wheel being 13.71°. This ensures that the vehicle can make turns with optimal smoothness and stability. Ackerman Angle Analysis for a Tire Slip Angle of 7.35° confirms that this steering system design is successful in optimizing vehicle performance in various turning conditions. Overall, the design of this steering system satisfies the essential technical requirements for urban electric vehicles, increasing efficiency and effectiveness in energy use and ensuring user safety.